2015
DOI: 10.1002/2015jg003057
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen reduction pathways in estuarine sediments: Influences of organic carbon and sulfide

Abstract: Potential rates of sediment denitrification, anaerobic ammonium oxidation (anammox), and dissimilatory nitrate reduction to ammonium (DNRA) were mapped across the entire Niantic River Estuary, CT, USA, at 100–200 m scale resolution consisting of 60 stations. On the estuary scale, denitrification accounted for ~ 90% of the nitrogen reduction, followed by DNRA and anammox. However, the relative importance of these reactions to each other was not evenly distributed through the estuary. A Nitrogen Retention Index … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
36
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 71 publications
6
36
1
Order By: Relevance
“…Our present study provides insights into eutrophic freshwater systems by documenting the interdependence of sulfide and nitrate, as well as the presence of anammox organisms in this engineered wetland. A recent study investigating nitrogen reduction pathways in estuarine sediments found no correlation between anammox and DNRA rates and sulfide (56); however, that finding was counter to results of a study focusing on the same location that found anammox bacterial abundance positively correlated to percent organic carbon and sulfide concentration (57). DNRA has been previously linked to sulfide oxidation in marine environments (58) and has been directly coupled to anammox in marine sediments and enrichment cultures (17,59).…”
Section: Figcontrasting
confidence: 49%
“…Our present study provides insights into eutrophic freshwater systems by documenting the interdependence of sulfide and nitrate, as well as the presence of anammox organisms in this engineered wetland. A recent study investigating nitrogen reduction pathways in estuarine sediments found no correlation between anammox and DNRA rates and sulfide (56); however, that finding was counter to results of a study focusing on the same location that found anammox bacterial abundance positively correlated to percent organic carbon and sulfide concentration (57). DNRA has been previously linked to sulfide oxidation in marine environments (58) and has been directly coupled to anammox in marine sediments and enrichment cultures (17,59).…”
Section: Figcontrasting
confidence: 49%
“…Although high inputs of NH 4 + provide the substrate for nitrification, the anaerobic condition of sediments may inhibit this process. The rates of anammox, DNRA, nitrogen fixation, and nitrification in this study were comparable to other ecosystems (Andersson et al, ; Billen, ; Gardner et al, ; Hou et al, , ; Jin et al, ; Kim et al, ; Li & Lang, ; McCarthy et al, ; Plummer et al, ; Scott et al, ; Song et al, ; Zhao et al, ) (Table S2). Overall, compared to other aquatic environments, urban river network with extensive inputs of NH 4 + has changed from a source to a sink of NH 4 + , which helps remove NH 4 + a pollution.…”
Section: Discussionsupporting
confidence: 86%
“…Co-occurrence of denitrification and DNRA in artificial wastewater treatment wetlands and natural ecosystems, such as sediments, is often reported in literature (Mørkved et al, 2005; Giblin et al, 2013; Hardison et al, 2015). To which extent the Ac/N ratio dependent co-occurrence of DNRA and denitrification is influenced by the nature of the electron donor/carbon source in the system (Giblin et al, 2013; Plummer et al, 2015) and the oxidized nitrogen compound utilized (i.e., nitrite or nitrate), will be the topic of future studies. In addition, spatial heterogeneities in the environment could affect the co-occurrence (Verhagen and Laanbroek, 1991).…”
Section: Discussionmentioning
confidence: 99%